Relevance of the world health organization in a multipolar world in solving global health challenges - Ranjit Kumar Dehury (Frontiers Media S.A., 2022)
There have been many criticisms about the World Health Organization (WHO) in the last decade. In a multipolar world, there are rivalries between nations and geopolitical regions. However, health issues remain outside the murky world of politics due to their far-reaching consequences on human society. The power conferred on the WHO is very significant in protecting the health and well-being of the global population. As a neutral organization, the WHO is supposed to uphold people's rights to health, especially in controlling diseases of international importance. The paper highlighted the significant roles of the WHO in leadership issues, research and development, solving disputes among countries, providing resources for low-performing regions, regulating international health laws, responding to a humanitarian crisis, and communicating during the crisis. Further, evidence from global literature critically analyzed the enforcement role of WHO on international health regulations (IHRs).